PERBANDINGAN HASIL MIKROSKOPIS LANJUTAN PENDERITA TBC PARU SETELAH PENGOBATAN DENGAN RIWAYAT DM DAN TANPA DM DI PUSKESMAS KEDUNDUNG - Esti Rizkiana Pratiwi; Frida Luthfia Mari; Halik Wijaya; Titik Sundari; Indra Adi Wira Prasetya (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2023)
Comorbid diabetes mellitus (DM) in pulmonary tuberculosis (TB) patients may increase the risk of death even with or during TB treatment. Immunocompromised conditions due to DM increase the risk of infection and sputum conversion failure. The risk of recurrence in comorbid patient is also higher after treatment. Objective of this research is to describe the comparison of further microscopic examination of pulmonary tuberculosis patients without DM and pulmonary tuberculosis patients with a history of diabetes at the Kedundung Public Health Center. The study was conducted by observing each of 15 TB positive sputum samples accompanied by a history of DM and those without any history of DM 2 months post-treatment on further microscopic examination. Further microscopic examination showed that 100% of sputum samples of TB patients without a history of DM and receiving treatment gave negative results, while sputum samples of TB patients with DM history and receiving treatment, while sputum samples of patients who had received treatment showed results of 2+ by 80% and 3+ by 20% and there were no negative results for TB. These results prove that there is an effect of a history of DM disease on TB treatment outcomes. Keywords : Further microscopic examination, Pulmonary tuberculosis (TB), Diabetes Mellitus (DM)